Bacteriocin-Nanoconjugates (Bac10307-AgNPs) Biosynthesized from Lactobacillus acidophilus-Derived Bacteriocins Exhibit Enhanced and Promising Biological Activities - Arif Jamal Siddiqui; Mitesh Patel; Mohd Adnan; Sadaf Jahan; Juhi Saxena; Mohammed Merae Alshahrani; Abdelmushin Abdelgadir; Fevzi Bardakci; Manojkumar Sachidanandan; Riadh Badraoui; Mejdi Snoussi; Allal Ouhtit (MDPI AG, 2023)
The proteinaceous compounds produced by lactic acid bacteria are called bacteriocins and have a wide variety of bioactive properties. However, bacteriocin's commercial availability is limited due to short stability periods and low yields. Therefore, the objective of this study was to synthesize bacteriocin-derived silver nanoparticles (Bac10307-AgNPs) extracted from Lactobacillus acidophilus (L. acidophilus), which may have the potential to increase the bioactivity of bacteriocins and overcome the hurdles. It was found that extracted and purified Bac10307 had a broad range of stability for both temperature (20-100 °C) and pH (3-12). Further, based on Sodium dodecyl-sulfate polyacrylamide gel electrophoresis (SDS-PAGE) analysis, its molecular weight was estimated to be 4.2 kDa. The synthesized Bac10307-AgNPs showed a peak of surface plasmon resonance at 430 nm λmax. Fourier transform infrared (FTIR) confirmed the presence of biological moieties, and transmission electron microscopy (TEM) coupled with Energy dispersive X-Ray (EDX) confirmed that AgNPs were spherical and irregularly shaped, with a size range of 9-20 nm. As a result, the Bac10307-AgNPs displayed very strong antibacterial activity with MIC values as low as 8 μg/mL for Staphylococcus aureus (S. aureus) and Pseudomonas aeruginosa (P. aeruginosa), when compared to Bac10307 alone. In addition, Bac10307-AgNPs demonstrated promising in vitro antioxidant activity against 2,2-diphenyl-1-picrylhydrazyl (DPPH) (IC50 = 116.04 μg/mL) and in vitro cytotoxicity against human liver cancer cells (HepG2) (IC50 = 135.63 μg/mL), more than Bac10307 alone (IC50 = 139.82 μg/mL against DPPH and 158.20 μg/mL against HepG2). Furthermore, a protein-protein molecular docking simulation study of bacteriocins with target proteins of different biological functions was also carried out in order to ascertain the interactions between bacteriocins and target proteins.